Obesity Induces Disruption of Microvascular Endothelial Circadian Rhythm - Padgett, Caleb A.; Butcher, Joshua T.; Haigh, Steven B.; Speese, Andrew C.; Corley, Zachary L.; Rosewater, Cody L.; Sellers, Hunter G.; Larion, Sebastian; Mintz, James D.; Fulton, David J. R.; Stepp, David W. (Frontiers in Physiology, 2022)
Obese individuals are at significantly elevated risk of developing cardiovascular disease (CVD). Additionally, obesity has been associated with disrupted circadian rhythm, manifesting in abnormal sleeping and feeding patterns. To date, the mechanisms linking obesity, circadian disruption, and CVD are incompletely understood, and insight into novel mechanistic pathways is desperately needed to improve therapeutic potential and decrease morbidity and mortality. The objective of this study was to investigate the roles of metabolic and circadian disruptions in obesity and assess their contributions in promoting vascular disease. Lean (db/+) and obese (db/db) mice were subjected to 12 weeks of constant darkness to perturb circadian rhythm and were assessed for changes in metabolism, gene expression, and vascular function. Expression of endothelial nitric oxide synthase (eNOS), an essential enzyme for vascular health, was blunted in obesity and correlated with the oscillatory loss of the novel regulator cezanne (OTUD7B). Lean mice subjected to circadian disruption displayed marked reduction in vasodilatory capacity, while endothelial dysfunction of obese mice was not further compounded by circadian disruption. Endothelial gene expression of essential circadian clock components was altered in obesity, but imperfectly phenocopied in lean mice with circadian dysfunction, suggesting overlapping but separate mechanisms driving endothelial dysfunction in obesity and circadian disruption. Taken together, these data provide insight into the nature of endothelial circadian rhythm in obesity and suggest a distinct mechanism by which obesity causes a unique circadian defect in the vasculature.